حقيبة تعليمية مقترحة لتنمية مهارات ضبط وتوصيل التعليم لذوى الاحتياجات الخاصة والاتجاه نحو التدريس لهم بمدارس العاديين لدى معلمى الدراسات الإجتماعية ( الطالب المعلم ) - عبدالعال، رجاء محمد عبدالجليل (رابطة التربويين العرب, 2014)
هدفت الدراسة إلى بناء حقيبة تعليمية من أجل تنمية مهارات ضبط التعليم وتوصيله للتلاميذ ذوي الاحتياجات الخاصة لمعلمي الدراسات الاجتماعية (الطالب المعلم) واتجاهه نحو التدريس لهم، ولتحقيق هذا الهدف تم ما يلي: إعداد حقيبة تعليمية. إعداد بطاقة ملاحظة لقياس مستوى أداء الطالب المعلم لمهارات ضبط التعليم لذوي الاحتياجات الخاصة. إعداد بطاقة ملاحظة لقياس مستوى أداء الطالب المعلم لمهارات توصيل التعليم لذوي الاحتياجات الخاصة. إعداد مقياس لاتجاهات الطالب المعلم نحو التدريس لذوي الاحتياجات الخاصة. اختيار مجموعة الدراسة من قسم الدراسات الاجتماعية بالكلية ومن طلاب الدبلوم العام التربوي الذين لم يعملوا بمهنة التدريس والتحقوا بالدبلوم من أجل إعدادهم للعمل بمهنة التدريس. وقد أشارت نتائج الدراسة إلى: ارتفاع النسبة المئوية إلى أكثر من 75% لصالح التطبيق البعدي حيث وصلت النسبة المئوية لمهارات ضبط التعليم إلى 91.1 % وبلغت نسبة مهارات توصيل التعليم إلى 85.58% وبلغت النسبة المئوية للاتجاه نحو التدريس 81.4%. وجود فروق بين المتوسطات دالة إحصائيا عند مستوى 0.01 لكل مهارات ضبط التعليم وتوصيل التعليم ومقياس الاتجاه نحو التدريس. وجود نسبة كسب معدل في مهارات ضبط التعليم وصلت إلى 1.24 وهي نسبة تفوق نسبة الكسب المعدل لبليك وبلغت في مهارات توصيل التعليم 1.17 وهي نسبة تقترب من الحد الأعلى، وبلغت في الاتجاه نحو التدريس 920. وجود علاقة ارتباطية موجبة تامة بين مهارات ضبط التعليم والاتجاه نحو التدريس حيث وصل معامل الارتباط إلى 0.80، ووجود علاقة أكثر من متوسط بين مهارات توصيل التعليم والاتجاه نحو التدريس بلغت 0.55 This study aimed at constructing an instructional module for developing Social Studies prospective teachers ’ skills of management of learning and its delivery among students with special needs. It also aimed at developing their attitudes towards teaching special needs students. To achieve this aim, the study followed the following procedures: Constructing an instructional module. Designing an observation checklist for measuring prospective teachers’ delivery of learning skills and another one for measuring management of learning skills among special needs students. Designing an attitude scale for measuring prospective teachers ’ attitude towards teaching special needs students. Selecting the study population from the students at the General Diploma, the Social Studies section at the Faculty of Education, Banha University who did not work in teaching and enrolled in this diploma to get prepared for teaching. The results of the study indicated the following: The increase of the percentage to 75% in favor of the post-test of learning management skills, delivery learning skills and attitude towards teaching. The percentage of management of learning reached 91%, delivery of learning reached 85.58% and attitudes towards teaching reached 82.4% There was a statistically significant difference at 0.01 level in management of learning skills and delivery learning skills and attitudes towards teaching. The modified gain ratio for the management of learning reached 1.24, which is more than Black’s ration. Besides, it reached 1.17 in delivery of learning skills, which is close to the maximum level, and .92 in attitude towards teaching. There was a relationship between management of learning skills and attitudes towards teaching. The correlation coefficient reached 0.80. In addition, there was a relationship between delivery of learning skills and attitudes towards teaching (r = 0.55).
Keywords: التدريس -- التربية الخاصة -- الحقائب التعليمية -- ذوى الإحتياجات الخاصة -- الطالب المعلم -- الدراسات الإجتماعية